Transforming vocational education and training using AI - Ĉela, Eriona [Herausgeber]; Vajjhala, Narasimha Rao [Herausgeber]; Potluri, Rajasekhara Mouly [Herausgeber]; Eappen, Philip [Herausgeber] (IGI Global, 2025)
"Vocational Education and Training (VET) is evolving with the advancements made in artificial intelligence (AI). There is a need to transform the existing VET programs that are following a traditional model into a dynamic and AI-enhanced learning environment as industries are increasingly using AI technologies. In the areas of automation and AI, major changes have taken place resulting in a skill gap that can be addressed by modernizing the existing VET programs. Further research into AI integration may help foster lifelong learning opportunities and empower vocational educators to help students thrive in a digital world. Transforming Vocational Education and Training Using AI examines the need for updating VET with AI to prepare the future workforce with the necessary skillsets. It addresses the gap in the current educational frameworks and presents innovative strategies and practical applications highlighting how AI can be used to improve delivery of VET programs. This book covers topics such as cybersecurity, e-learning, and career training, and is a useful resource for business owners, computer engineers, researchers, scientists, academicians, and educators." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: G 2.2.1 Technologisierung; G 2.2.2 Internet / Mediengesellschaft; 370; Berufsbildung; Künstliche Intelligenz; Virtuelle Realität; Augmented Reality; E-Learning; Digitalkompetenz; Medienkompetenz